2015
DOI: 10.1039/c5cp01981h
|View full text |Cite
|
Sign up to set email alerts
|

Controlling pyridinic, pyrrolic, graphitic, and molecular nitrogen in multi-wall carbon nanotubes using precursors with different N/C ratios in aerosol assisted chemical vapor deposition

Abstract: Nitrogen-containing multi-wall carbon nanotubes (N-MWCNTs) were synthesized using aerosol assisted chemical vapor deposition (CVD) techniques in conjunction with benzylamine:ferrocene or acetonitrile: ferrocene mixtures. Different amounts of toluene were added to these mixtures in order to change the N/C ratio of the feedstock. X-ray photoelectron and near-edge X-ray absorption fine structure spectroscopy detected pyridinic, pyrrolic, graphitic, and molecular nitrogen forms in the N-MWCNT samples. Analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 47 publications
3
33
0
1
Order By: Relevance
“…A rise of the low-energy component and the high-energy component in the spectrum of the annealed N-graphene supposes the transformation of the pyrrolic N in the pyridinic N and graphitic N, respectively. At the excitation energy of 830 eV, the mean free path of the N 1s photoelectrons allows probing about five graphene layers [51]. Thus, the spectra measured at this energy provide information about nitrogen distributed in all layers of the N-graphene film.…”
Section: Resultsmentioning
confidence: 99%
“…A rise of the low-energy component and the high-energy component in the spectrum of the annealed N-graphene supposes the transformation of the pyrrolic N in the pyridinic N and graphitic N, respectively. At the excitation energy of 830 eV, the mean free path of the N 1s photoelectrons allows probing about five graphene layers [51]. Thus, the spectra measured at this energy provide information about nitrogen distributed in all layers of the N-graphene film.…”
Section: Resultsmentioning
confidence: 99%
“…Ombaca et al [55] reported that N-pyrrolic configuration in carbon nanotubes improves the palladium catalytic properties because it introduces a better catalytic activity in the carbon material. Bulusheva et al [56] synthesized N-MWCNTs by AACVD method using ferrocene as catalytic precursor and benzylamine or acetonitrile as nitrogen and carbon precursors. Their results revealed that the concentration ratio N/C is determinant for how the nitrogen is incorporated into the lattice of carbon nanotubes.…”
Section: Introductionmentioning
confidence: 99%
“…Since duration of synthesis was the same for all samples, the rate of CN x nanotube growth is influenced by the temperature. The CCVD synthesis of nanotubes includes three stages: (i) decomposition of precursor on a catalytic surface, (ii) diffusion of the cracking products through the bulk and/or subsurface layers of a catalyst, and (iii) precipitation of these species in a tubular form . We conclude that in our synthesis conditions the optimal temperature for these processes is 800–850 °C.…”
Section: Resultsmentioning
confidence: 84%